Radical Scavenging and Antimicrobial Activities of Convolvulus microphyllus - Jain, R.; Pancholi, B.; Jain, S.C. (Asian Journal of Chemistry, 2011)
Convolvulus microphyllus Sieb. (family: convolvulaceae) is reported to be brain tonic and useful in CNS disorder. Powdered whole plant material was sequentially extracted with petroleum ether, ethyl acetate, methanol and water, dried in vacuo and weighed (%). Later, each of these extracts was tested for antioxidant (DPPH and FRAP method) and antimicrobial potentials (agar well diffusion method). Interestingly, ethyl acetate extract showed appreciable results (IC50 0.07 mg/mL, % inhibition 93.46) followed by the methanol extract (IC50 0.075 mg/mL, % inhibition 92.43) in DPPH method. In FRAP method, water extract was potentially active having antioxidant capacity 460 ± 7.64 ascorbic acid equivalent/mg extract. In antimicrobial activities, the ethyl acetate extract demonstrated appreciable activity against C. albicans and P. chrysogenum (IZ 20.00 ± 1.52 mm and 19.00 ± 1.00 mm respectively) followed by its methanol extract. Further, from its ethyl acetate and methanolic extracts different phenolic acids namely caffeic acid, p-coumaric acid, ferulic acid, gallic acid, vanillic acid and syringic acid were isolated.